Penerapan Asas Proporsionalitas dalam Perjanjian Bisnis di Indonesia - Bassaf Rizky Iqbal Bagaskara (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
The principle of proportionality plays an important role in ensuring a balance of rights and obligations between the parties to a reciprocal agreement. In the context of Indonesian contract law, this principle serves as a mechanism to prevent imbalances that could harm one of the parties, especially in commercial and complex contracts. This study uses a normative juridical approach with a literature review method, which involves analysis of relevant laws and regulations and case studies. This approach allows researchers to explore the application of the principle of proportionality in various types of reciprocal agreements, including franchise agreements and construction service contracts. For example, a study by Susanto et al. (2021) highlights how the principle of proportionality is applied in construction service contracts to ensure a fair distribution of responsibilities between contractors and clients. The results of the analysis show that the consistent application of the principle of proportionality can improve fairness in contractual relationships. In franchise agreements, the application of this principle helps to create a balance between the rights and obligations of the franchisor and franchisee, who often have different bargaining positions. Thus, the principle of proportionality serves not only as a legal principle, but also as a practical tool for achieving fairness in contractual practice